Giving asia her educational due - Joseph, Samatha (2012)
ECONOMICS plays a prime pragmatic role when it comes to considering graduate studies in Asia. With the Eurozone crisis affecting not only the ability of many European governments to keep their economies afloat, but also the purchasing power of its individual citizens,it is no surprise that students who wish to pursue their studies in Europe or other high-income nations will find themselves in a financial quandary.